PERANCANGAN MULTIMEDIA SEBAGAI MEDIA SOSIALISASI SOP KEPADA KARYAWAN PT. TRANSCON INDONESIA - HUTOMO SETIA BUDI (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2017)
Every firm or organization usually has a specific procedure in performing its activity. To make it easier in organizing events that occur repeatedly within a firm or organization, standardized activities are needed. Standardization procedure in a company is commonly called the SOP (Standard Operating Procedure). The SOP of the activities should be conveyed to all parties involved so that they can understand and execute the procedure according to applicable standards.Â The research methods used are qualitative method and literature studies conducted by collecting information in in-depth interviews from the internal party of PT. Transcon Indonesia. The presentation is designed in a multimedia form that combines audio, visual, and animation elements with flat design style, considered appropriate to deliver topical SOP presentation.Â Keywords: multimedia; presentation; SOP Â